Dureza superficial y resistencia a la compresión de materiales de restauración para dientes posteriores - Yanac - Acedo, Lourdes Magdalena (2025)
Objective: To compare the in vitro surface hardness and compressive strength of three direct restorative materials for posterior teeth. Methodology: This is a cross-sectional comparative experimental in vitro study. The sample consisted of 60 cylinders divided into three groups of 20 samples: Tetric N-Ceram Bulk Fill resin, Alkasite Cention-N, and Giomer Beautifil II, which were prepared using a Teflon matrix that served as a mold to prepare cylinders with the restorative materials according to ISO 4049 standards. Surface hardness was measured using the Vickers hardness tester, while compressive strength was determined with the Universal Testing Machine, measured in Megapascals. Results: The obtained values for surface hardness showed that Beautifil II had the highest average with 66.36 Vickers, while Cention-N obtained 48.54 Vickers, and Tetric N-Ceram Bulk Fill 48.22 Vickers. Regarding compressive strength, the highest average was for Tetric N-Ceram Bulk Fill with 217.35 Megapascals, followed by Beautifil II with 195.83 Megapascals, and Cention-N with 187.55 Megapascals. Conclusion: Giomer Beautifil II presented the highest surface hardness, while Tetric N-Ceram Bulk Fill resin achieved the highest compressive strength. Conversely, Alkasite Cention-N obtained the lowest values for both mechanical properties.